2016
DOI: 10.5796/electrochemistry.84.420
|View full text |Cite
|
Sign up to set email alerts
|

SnS<sub>2</sub> Urchins as Anode Material for Lithium-ion Battery

Abstract: SnS 2 urchins self-assembled by one dimensional nanorods, being different from the two dimensional flakes, were synthesized by a facile method to work as an anode material in lithium-ion battery. The SnS 2 urchins displayed a stable capacity of 600 mAh g −1 at the current density of 100 mA g −1 after 50 cycles. The SnS 2 urchins showed better cyclic performance and rate capacity compared with SnS 2 flakes. The improved performance was ascribed to the three dimensional structures which can decrease the volume e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Author: However, reports have clearly stated that pure SnS 2 (or MoS 2 ) possesses inherent low electrical conductivity and also is accompanied by irreversible volume expansion during the cycling, which eventually results in poor performance. 7,8 Highly conductive and flexible graphene is a superior choice to ameliorate LIBs' capability. Several groups' research discovered that diverse nanostructures complexes of LMS and graphene prepared through different methods (e.g., microwave, solvothermal, and chemical vapor deposition) exhibited better rate performance, longer cycle life, and better cycle stability than pristine LMS.…”
Section: Introductionmentioning
confidence: 99%
“…Author: However, reports have clearly stated that pure SnS 2 (or MoS 2 ) possesses inherent low electrical conductivity and also is accompanied by irreversible volume expansion during the cycling, which eventually results in poor performance. 7,8 Highly conductive and flexible graphene is a superior choice to ameliorate LIBs' capability. Several groups' research discovered that diverse nanostructures complexes of LMS and graphene prepared through different methods (e.g., microwave, solvothermal, and chemical vapor deposition) exhibited better rate performance, longer cycle life, and better cycle stability than pristine LMS.…”
Section: Introductionmentioning
confidence: 99%
“…11 Nevertheless, severe capacity fading of SnS 2 electrodes generally occurs due to low electrical conductivity (<10 À2 S cm À1 ), large volume change ($200%) during electrochemical cycling together with aggregation of SnS 2 , and in situ formation of the alloy phase (Li x Sn, 0 # x # 4.4). 7,12 Among several approaches to resolve these issues, formulating composites with carbon-based materials, especially graphene, has been fruitful. On one hand, excellent conductivity of graphene increases the conductivity of the composites and improves the anode performance.…”
Section: Introductionmentioning
confidence: 99%
“…Among these three products, 3D urchins have been shown to exhibit higher electrochemical surface area ( Figure a–f). [ 77 ] In addition, a variety of flower‐like hierarchical structures of sizes ranging from 3 µm to 20 nm have been reported under different temperatures (140, 160, and 180 °C), and the results showed that higher temperatures are suitable for the formation of the layered nanoparticle (NP) structures (Figure 3g–i). [ 78 ] Wang et al [ 79 ] reported that temperature has a significant effect on the crystallinity and the thickness of the SnS 2 nanoplates.…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…a–f) are adapted with permission. [ 77 ] Copyright 2016, The Electrochemical Society of Japan. g–i) Adapted with permission.…”
Section: Synthesis Methodsmentioning
confidence: 99%